2006
DOI: 10.1051/alr:2006016
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of some aquatic species with the organochlorine pesticide chlordecone in Martinique

Abstract: Martinique is a French overseas department whose economy relies heavily on agriculture. Organochlorine pesticides, mainly chlordecone, were used for banana cultivation to eradicate banana weevil over a period of 40 years. Chlordecone is chemically stable,and has a strong affinity for fatty tissues. It is therefore able to bioaccumulate in animals and thereby represent a threat to ecosystems and man. Soils from banana plantations in Martinique are heavily contaminated with chlordecone. Possible transfer of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Onions (AFSSA, 2007) and crustaceans (Coat et al, 2006) have both been found to be contaminated by chlordecone in monitoring studies. We cannot rule out the possibility that the selection of some food in the EWM as positively or negatively associated with blood chlordecone levels may be due to their correlation with other potential predictors in dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Onions (AFSSA, 2007) and crustaceans (Coat et al, 2006) have both been found to be contaminated by chlordecone in monitoring studies. We cannot rule out the possibility that the selection of some food in the EWM as positively or negatively associated with blood chlordecone levels may be due to their correlation with other potential predictors in dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Among the total of 1800 t of CLD produced over time in the world, one sixth was spread in Martinique and Guadeloupe (but to a lesser extent in that second case) (Le Déaut and Procaccia 2009). This led to severe contamination of soils (Cabidoche et al 2009), surface waters and groundwater (respectively, Franco 2005 andGourcy et al 2009), plant products (Cabidoche and LesueurJannoyer 2012), fresh water and seafood (Coat et al 2006 and, and livestock (e.g. Jondreville et al 2014) and wildlife (Cavelier 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In the French West Indies (FWI), the tropical climate promotes the rapid development of pests which exerts significant pressure on crops leading to the use of considerable amounts of pesticides in these regions (Bocquené and Franco, 2005). The use of organochlorine pesticides first started in the 1950's and led to widespread contamination of the environment (Coat et al, 2006). Because of their physicochemical properties, organochlorine pesticides are persistent in the environment and are known to be accumulated along food chains, resulting in pronounced ecotoxicological damage (Cailleaud et al, 2009;Matsumura, 1975).…”
Section: Introductionmentioning
confidence: 99%